Measurement Properties of Gait-Related Outcomes in Youth With Neuromuscular Diagnoses: A Systematic Review. Issue 8 (1st August 2014) - Ammann-Reiffer, Corinne; Bastiaenen, Caroline H.G.; de Bie, Rob A.; van Hedel, Hubertus J.A.
Abstract : Background: Sound measurement properties of outcome tools are essential when evaluating outcomes of an intervention, in clinical practice and in research. Purpose: The purpose of this study was to review the evidence on reliability, measurement error, and responsiveness of measures of gait function in children with neuromuscular diagnoses. Data Sources: The MEDLINE, CINAHL, EMBASE, and PsycINFO databases were searched up to June 15, 2012. Study Selection: Studies evaluating reliability, measurement error, or responsiveness of measures of gait function in 1- to 18-year-old children and youth with neuromuscular diagnoses were included. Data Extraction: Quality of the studies was independently rated by 2 raters using a modified COnsensus-based Standards for the selection of health status Measurement INstruments (COSMIN) checklist. Studies with a fair quality rating or better were considered for best evidence synthesis. Data Synthesis: Regarding the methodological quality, 32 out of 35 reliability studies, all of the 13 measurement error studies, and 5 out of 10 responsiveness studies were of fair or good quality. Best evidence synthesis revealed moderate to strong evidence for reliability for several measures in children and youth with cerebral palsy (CP) but was limited or unknown in other diagnoses. The Functional Mobility Scale (FMS) and the Gross Motor Function Measure (GMFM) dimension E showed limited positive evidence for responsiveness in children with CP, but it was unknown or controversial in other diagnoses. No information was reported on the minimal important change; thus, evidence on measurement error remained undetermined. Limitations: As studies on validity were not included in the review, a comprehensive appraisal of the best available gait-related outcome measure per diagnosis is not possible. Conclusions: There is moderate to strong evidence on reliability for several measures of gait function in children and youth with CP, whereas evidence on responsiveness exists only for the FMS and the GMFM dimension E.